Observation of the Tetragonal-Orthorhombic transition in polycrystalline YBa2Cu3O6+δ samples during the oxidation process at constant temperature via thermogravimetry and differential thermometry analysis - Gallo, Lorenzo (2024)
This work examines the oxygenation process of polycrystalline powder of YBa2Cu3O6+δ through constant temperature thermogravimetric analysis. Starting from completely deoxygenated samples ( δ = 0), both the mass evolution in an oxygen atmosphere and a differential temperature value referenced to an inert sample (alumina powder) subjected to the same experimental conditions are recorded. The oxygenation process itself is identified as an exothermic process accompanied by a second also exothermic associated process. This second process is identified as the Tetragonal-Orthorhombic transition present in the material. Based on the obtained results, the structural phase diagram of the material is reconstructed. Issues of metastability of the structural phases, as well as the potential of the equipment used to obtain these results comparable to those obtained in large facilities, are discussed. Reinterpretations of previously discussed works in the literature are inferred.